Analyzing big data of da'wah manuscripts based on Dimensions: Mapping research on da'wah on social media - Karim, Abdul; Riyadi, Agus (Jurnal Ilmu Dakwah, 2024)
Purpose – This study aimed to explore big data analysis on social media da'wah manuscripts to understand and gain deeper insights into the phenomenon of da'wah in the digital era.Method – Using the big data analysis method, this study describes the main trends, interaction patterns, and impact of da'wah-themed texts on social media. Data was collected from the Dimension indexer as it is one of the platforms recognized by Arjuna (a national journal accreditation agency), and it is able to identify the most discussed and cited articles as well as other interaction analyses.Result – This big data analysis provides a deep understanding of the dynamics of the study of da'wah on social media. This allows us to see how da'wah messages on social media are adapted, accepted, and used by society in a digital context.Implication – This article details the implications of big data analysis findings for developing da'wah studies in social media. It presents potential future research directions to enrich our understanding of the dynamics of da'wah in the digital age.Originality/Value – This article makes a new contribution by examining extensive data from da'wah manuscripts through the Dimensions platform to track da'wah research on social media. This study stands out for its fresh method of merging big data analysis with Dimensions-indexed data, an area that has not been thoroughly investigated.***Tujuan – Tujuan dari penelitian ini adalah untuk mengeksplorasi analisis big data pada naskah dakwah di media sosial sebagai sarana untuk memahami dan mendapatkan wawasan yang lebih dalam tentang fenomena dakwah di era digital.Metode – Dengan menggunakan metode analisis big data, penelitian ini mendeskripsikan tren utama, pola interaksi, dan dampak dari teks-teks bertema dakwah di media sosial. Data dikumpulkan dari pengindeks Dimensions karena merupakan salah satu platform yang diakui oleh Arjuna (lembaga akreditasi jurnal nasional), dan mampu mengidentifikasi artikel yang paling banyak dibicarakan, paling banyak dikutip, serta analisis interaksi lainnya.Hasil – Hasil dari analisis big data ini memberikan pemahaman yang mendalam tentang dinamika studi dakwah di media sosial, yang memungkinkan kita untuk melihat bagaimana pesan-pesan dakwah di media sosial diadaptasi, diterima, dan digunakan oleh masyarakat dalam konteks digital.Implikasi – Artikel ini merinci implikasi dari temuan analisis big data untuk pengembangan studi dakwah di media sosial dan menyajikan potensi arah penelitian di masa depan untuk memperkaya pemahaman kita tentang dinamika dakwah di era digital.Orisinalitas/Nilai – Artikel ini memberikan kontribusi baru dengan mengkaji data ekstensif dari naskah dakwah melalui platform Dimensions untuk melacak penelitian dakwah di media sosial. Penelitian ini menonjol karena menggunakan metode optimum dalam menggabungkan analisis data besar dengan data yang diindeks oleh Dimensions.